Juvenile–adult tree associations in a continental Mediterranean ecosystem: no evidence for sustained and general facilitation at increased aridity - Granda, Elena; Escudero, Adrián; de la Cruz, Marcelino; Valladares, Fernando (Journal of Vegetation Science, 2012)
Question How do tree species identity, microhabitat and water availability affect inter- and intra-specific interactions between juvenile and adult woody plants? Location Continental Mediterranean forests in Alto Tajo Natural Park, Guadalajara, Spain. Methods A total of 2066 juveniles and adults of four co-occurring tree species were mapped in 17 plots. The frequency of juveniles at different microhabitats and water availability levels was analysed using log-linear models. We used nearest-neighbour contingency table analysis of spatial segregation and J-functions to describe the spatial patterns. Results We found a complex spatial pattern that varied according to species identity and microhabitat. Recruitment was more frequent in gaps for Quercus ilex, while the other three species recruited preferentially under shrubs or trees depending on the water availability level. Juveniles were not spatially associated to conspecific adults, experiencing segregation from them in many cases. Spatial associations, both positive and negative, were more common at higher water availability levels. Conclusions Our results do not agree with expectations from the stress-gradient hypothesis, suggesting that positive interactions do not increase in importance with increasing aridity in the study ecosystem. Regeneration patterns are species-specific and depend on microhabitat characteristics and dispersal strategies. In general, juveniles do not look for conspecific adult protection. This work contributes to the understanding of species co-existence, proving the importance of considering a multispecies approach at several plots to overcome limitations of simple pair-wise comparisons in a limited number of sites.
Keywords: faginea; Juniperus thurifera; patterns; Pinus nigra; Quercus; Quercus faginea; Quercus ilex; Regeneration; spatial; spatial patterns; Stress-gradient hypothesis; water; Water availability

Differential light responses of Mediterranean tree saplings: linking ecophysiology with regeneration niche in four co-occurring species (Tree Physiology, 2006)
The ecophysiological mechanisms underlying plant–plant interactions and forest regeneration processes in Mediterranean ecosystems are poorly understood, and the experimental evidence for the role of light availability in these processes is particularly scant. We analyzed the effects of high and low irradiances on 31 ecological, morphological and physiological variables in saplings of four late-successional Mediterranean trees, two deciduous (Acer opalus subsp. granatense (Boiss.) Font Quer & Rothm. and Quercus pyrenaica Willd.) and two evergreen (Pinus nigra Arnold subsp. salzmannii (Dunal) Franco and Quercus ilex L.), which coexist in mature montane forests. Species differed in both their capacity to withstand high radiation and in their shade tolerance. The two deciduous species were the least tolerant to high radiation, exhibiting both dynamic and chronic photoinhibition in full sunlight, with severe implications for gas exchange and photosynthetic performance. Excess light severely limited the survival of A. opalus subsp. granatense, even minor reductions of excessive radiation (from full sunlight to 80% sunlight) being crucial for sapling survival. Among species, P. nigra was the most tolerant of high irradiances but showed the poorest shade acclimation. Interspecific differences in the mechanisms of response to light provide a partial explanation of the differential regeneration patterns previously reported for these species, with shade-tolerant plants (i.e., deciduous broadleaf species) benefiting the most from associations with nurse plants. We conclude that light availability is an important environmental factor defining the regeneration niche of Mediterranean woody species.
10.1093/treephys/26.7.947